Blockchain and digital governance: Decentralization of decision making policy. - Kassen, Maxat (Review of Policy Research, 2025)
Blockchain is gaining popularity as a potential solution for the decentralized management of public information. A number of interesting solutions have been proposed by independent developers around the world to promote blockchain as a promising platform to potentially accelerate democratic processes and achieve certain public values in reforming digital governance. This could be reflected in facilitating direct citizen participation in digital politics, promoting greater civic cooperation and engagement in political discussions, boosting the role of civic commentary and even collaborative decision‐making in e‐government. In this regard, the article critically elaborates on the potential of this technology to promote political dimensions of public sector reforms in a post‐positivist manner, resorting to the analysis of concrete e‐participation cases in a number of public areas where the potential has already been realized and the opinions of professional software developers who are currently engaged in building various blockchain‐driven data management solutions in the e‐government area. This paper identifies, debates, and draws on what benefits and risks public policy can yield from the implementation of blockchain governance.